(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research article investigates the relationship between green marketing and the Millennial generation’s sustainable consumption patterns. Through an extensive review of literature spanning from 2019 to 2023, combined with primary data collection involving surveys and secondary data analysis, the study explores the driving factors and barriers influencing Millennials’ engagement with eco-friendly products and practices. The research contributes to a better understanding of the effectiveness of green marketing strategies in shaping sustainable behaviors among Millennials, offering insights for businesses aiming to target this environmentally-conscious demographic.